TRANSPLANTASI PENGATURAN RESALE RIGHTS (DROIT DE SUITE) PRANCIS KE DALAM SISTEM HUKUM HAK CIPTA INDONESIA - Syakura, Abdan; Wicaksono, Rifki Alfian; Madani , A. Iqbal; Riswandi , Budi Agus (JIPRO: Journal of Intellectual Property, 2024)
The concept of droit de suite or the right to receive royalties from the resale of a work (resale royalty rights) for artists is designed so that it can be used as a system to provide a portion of the increase in the value of the work to the artist when his work is resold. In the regulation of the copyright law system in Indonesia, the principle of droit de suite does not yet have a specific arrangement as part of the moral rights contained in Law No. 28 of 2014 concerning Copyright (UUHC), even though the condition for implementing droit de suite is that the state must give permission and legally recognize the droit de suite in the laws and regulations. This study uses a juridical normative method and uses the Statute Approach and the Conceptual Approach which are analyzed descriptively. The results of the study indicate that there is a need for harmony with the resale rights law which will be carried out by transplanting the law into Indonesian law.